Total antioxidant power in some species of Labiatae : adaptation of FRAP method - Szőllősi, Réka; Szőllősi Istvánné Varga, Ilona (Acta Biologica Szegediensis, 2002)
Medicinal plants have a lot of type antioxidants, mostly polyphenols, flavonoids which exhibit high antioxidant activity (Rice-Evans et al. 1995). The intake of antioxidants present in food is an important health-protecting factor. Herbal compounds known by ancient medicine are of growing interest in the domain of prevention of diseases. The FRAP assay (ferric reducing ability of plasma), a simple test of the total antioxidant power have been chosen to assess the presumable effects of some kind of tea and medicinal plant. The aim of our work was to get answer for the question: is this method applicable for investigation of fresh plant samples and herbs? FRAP assay depends upon the ferric tripyridyltriazine (Fe(III)-TPTZ) complex to the ferrous tripyridyltriazine (Fe(II)-TPTZ) by a reductant at low pH. Fe(II)-TPTZ has an intensive blue colour and can be monitored at 593 nm. (Benzie and Strain 1996). Several species of medicinal plants were involved in our investigations: from Labiatae family Melissa officinalis, Mentha piperita, Ocimum basilicum, Salvia officinalis, Satureja hortensis and Majoranna hortensis. Our results show that FRAP method is sensitive in the measurement of total antioxidant power of fresh biological fluids, such as plant homogenates and pharmacological plant products. Antioxidant activity of our samples were confirmed with in vitro model system.